ANALISIS KESULITAN BELAJAR MATEMATIKA PADA ANAK BERKEBUTUHAN KHUSUS TUNAGRAHITA RINGAN KELAS IV SDN PERWIRA - Chairunisa; Ratih Purnamasari; Yudhie Suchyadi (STKIP Subang, 2023)
Education is a basic need for humans to achieve an expected goal, because without education we will not be able to develop the potential of ourselves optimally both cognitive, pricomotor and affective. Education is realized through the teaching and learning process. The government states that every citizen has the same right to receive quality education and citizens with physical, emotional, mental, intellectual and social disabilities are entitled to special education. Education is needed to develop the potential of children with special needs for their survival which must always be dynamic and optimistic. As a prospective teacher, you should know the learning difficulties experienced by students in class, especially the difficulties of students in learning mathematics. The purpose of this study was to determine the factors of difficulty in learning mathematics for children with special needs for mild intellectual impairment. The subjects of the study were 1 grade IV student with the initiative